Math, asked by satyendrasingh289198, 3 months ago

6(ax+by)=3a+2b , 6(ax-by)=3b-2a​ , find it by elimination method​

Answers

Answered by krishnamishrakdl
0

Step-by-step explanation:

The given equations are 6(ax + by) = 3a + 2b ⇒6ax + 6by = 3a + 2b ………(i) and 6(bx – ay) = 3b – 2a ⇒6bx – 6ay = 3b – 2a ………(ii) On multiplying (i) by a and (ii) by b, we get Hence, the required solution is x = 1/2 and y = 1/3.Read more on Sarthaks.com - https://www.sarthaks.com/130711/solve-for-x-and-y-6-ax-by-3a-2b-6-bx-ay-3b-2a

Answered by priyanshgahlot2
0

Answer:

answer is 5a-b nbaki calculation tu kar le

Similar questions